PETA STATISTIK PDB NASIONAL INDONESIA 2025–2026: ANALISIS DESKRIPTIF STRUKTUR PERTUMBUHAN EKONOMI, KONTRIBUSI SEKTOR UTAMA, DAN PROYEKSI NILAI NOMINAL BERDASARKAN DATA BPS, BI, SERTA IMF DALAM KONTEKS PEMULIHAN PASCA-PANDEMI - Ignatius Septo Pramesworo; Tehedi (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2026)
This article presents a descriptive analysis of statistical maps of Indonesia’s national Gross Domestic Product (GDP) for the period 2025–2026 based on primary data from the Central Statistics Agency (BPS), projections from Bank Indonesia (BI) and the International Monetary Fund (IMF), focusing on the structure of real economic growth averaging 5.1–5.3% (year-on-year), key sectoral contributions such as manufacturing (19–20%), trade (13–14%), agriculture (13–14%), and digital services (45% cumulative) which account for 63–65% of nominal GDP, and a projected value of Rp22,000–23,500 trillion by 2026 amidst the post-COVID-19 pandemic recovery. A systematic literature review reveals the dynamics of transformation from a commodity-based economy to one with high value-added through nickel downstreaming, continued PEN fiscal stimulus, and a stable BI-Rate monetary policy that maintains inflation at 2.5±1% and the rupiah at Rp15,500/USD, although regional disparities between Java and non-Java areas, as well as global geopolitical risks, remain key challenges. The findings underscore the resilience of the national economy towards Indonesia Emas 2045, with recommendations for inclusive reforms based on the digitalisation of SMEs, a green economy, and export diversification to sustain the momentum of sustainable growth above 5%.